2014
DOI: 10.1093/abbs/gmu081
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum oxidoreductin 1α mediates hepatic endoplasmic reticulum stress in homocysteine-induced atherosclerosis

Abstract: Endoplasmic reticulum (ER) stress is emerging as an important modulator of different pathological process and as a mechanism contributing to homocysteine (Hcy)-induced hepar injury. However, the molecular event that Hcyinduced ER stress in the hepar under the atherosclerosis background is currently unknown. Endoplasmic reticulum oxidoreductin 1a (ERO1a) plays a crucial role in maintaining ER stress function. In this study, we determined the expression of ERO1a in the hepar in hyperhomocysteinemia and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…In addition to the finding that Hcy reprograms mitochondrial metabolism, we found that Hcy also triggers ER stress in T cells, and inhibition of ER stress blocks Hcy-activated T cells, while stimulation of ER stress mimics this activation, suggesting that Hcy activates T cells by triggering ER stress. These results agree with the findings in vascular endothelial cells (Hossain et al, 2003 ), hepatocytes (Yang et al, 2014 ), neurons (Wei et al, 2014 ), and adipocytes (Li et al, 2013 ), where Hcy also causes ER stress. ER interacts with mitochondria forming dynamic networks across all cells to regulate multiple cellular processes (Bravo et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the finding that Hcy reprograms mitochondrial metabolism, we found that Hcy also triggers ER stress in T cells, and inhibition of ER stress blocks Hcy-activated T cells, while stimulation of ER stress mimics this activation, suggesting that Hcy activates T cells by triggering ER stress. These results agree with the findings in vascular endothelial cells (Hossain et al, 2003 ), hepatocytes (Yang et al, 2014 ), neurons (Wei et al, 2014 ), and adipocytes (Li et al, 2013 ), where Hcy also causes ER stress. ER interacts with mitochondria forming dynamic networks across all cells to regulate multiple cellular processes (Bravo et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…The endoplasmic reticulum is the primary organelle of the cell and its primary function is to be responsible for the folding of protein and to maintain cell homeostasis (23). The stimulation of certain physiological, biochemical and pathological factors can lead to oxidative stress, so as to affect protein folding, the accumulation of unfolded protein and the misfolding of proteins in the endoplasmic reticulum, which leads to ERS (21,24). It was previously determined that ERS was prevalent in tumor tissues (25).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is integrated together with DNA denaturation and bisulfite conversion processes into 1 step by the EZ DNA Methylation‐Gold TM Kit. Nested methylation‐specific PCR was used for the detection of methylation of ERO1α as previously described . The methylation primers used for methylmion specific PCR (MSP) are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that ER stress–mediated membrane expression of calreticulin/endoplasmic reticulum‐resident protein 57 (CRT/ERp57) induces cell apoptosis in drug‐resistant endometrial cancer cells. In our previous study, we found that ERO1α‐mediated ER stress is implicated in liver apoptosis in apolipoprotein‐E‐deficient (ApoE −/− ) mice …”
Section: Introductionmentioning
confidence: 99%